2023
DOI: 10.1186/s10086-023-02104-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal softening properties of various wood species within an annual ring

Hiroaki Horiyama,
Yuka Miyoshi,
Keisuke Kojiro
et al.

Abstract: Dynamic mechanical analysis (DMA) measurements of water-saturated earlywood (EW) and latewood (LW) of various wood species in the temperature range from 0 to 100 °C were focused to clarify the differences in thermal softening properties within an annual ring. The following results were obtained. The peak of tanδ caused by micro-Brownian motion of lignin was observed in both EW and LW all species. For softwoods, the peak temperatures of tanδ of EW appeared at higher temperatures than those of LW. For hardwoods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This relaxation has been attributed to the movement of water by several researchers and is known to be sensitive to the moisture content. 26,27 This peak for delignified wood moved slightly to −77 °C, signifying that the removal of lignin may have increased the moisture absorption capacity of the wood. In this light, it is likely that the shift of the β peak in modified wood is related to an increase in the moisture content.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This relaxation has been attributed to the movement of water by several researchers and is known to be sensitive to the moisture content. 26,27 This peak for delignified wood moved slightly to −77 °C, signifying that the removal of lignin may have increased the moisture absorption capacity of the wood. In this light, it is likely that the shift of the β peak in modified wood is related to an increase in the moisture content.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…When the temperature increased from 30 • C to 80 • C, the decrement in tensile modulus for LT-EW, LT-LW, TL-EW, and TL-LW was 32.4%, 29.1%, 84.0%, and 76.8%, respectively. Under water-saturated conditions, heat energy is provided for the Brownian motion of polymer molecules and chain segments, resulting in the decrement in tensile modulus with the rising temperature [11,12]. Accordingly, the decrements in tensile modulus for EW were larger than those for LW in both the L and T directions.…”
Section: Microfibril Angle (Mfa)mentioning
confidence: 99%
“…Numerous scholars have extensively explored the differences in the tensile mechanical properties between EW and LW at a given temperature and moisture content (MC) level [6][7][8][9][10][11][12]. Roszyk [7] reported on the tensile mechanical behavior of the EW and LW of pine wood (Pinus sylvestris) in the longitudinal (L) direction in the wet and air-dry states, and found that tensile strength, modulus of elasticity, and stress at the proportionality limit of EW and LW decreased generally as the MC increased.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations